The Influence of Religiosity and Social Support on Psychological Well-Being in Widows whose Husbands Die with Stress Coping as Intervening in District X, Semarang City - Viola, Winoni Rudy; Winta, Mulya Virgonita Iswindari; Widhiastuti, Hardhani (CV. Rayyan Dwi Bharata, 2025)
The status of widowed women is a heavy and difficult emotional challenge because they have to arrange and take care of their life needs and even the needs of their children by themselves, social support is an expression of individuals to provide support to others who have a connection and enough meaning in their lives, individuals who have a high level of religiosity are better able to interpret their life events positively so that they become more meaningful, avoid stress and depression. Coping stress can be interpreted as cognitive and behavioral adjustments towards a better state, reducing and tolerating existing demands that cause stress. the purpose of this study was to determine the effect of religiosity, social support with psychological well-being through coping stress.The sampling technique in this study used saturated samples. Saturated samples are used when the entire population is used as research subjects, this research approach uses quantitative methods with analysis using SEM-PLS. the results of this study indicate that: : 1) terdapat penagruh religiusitas dengan psychological well-being secara signifikan dan nilai p-value sebesar 0,0000,05. 2) terdapat pengaruh religiusitas dengan copings stress secara signifikan dan nilai p-value sebesar (0,0150,05). 3) Artinya terdapat pengaruh dukungan sosial dengan psychological well-being secara signifikan dan nilai p-value sebesar (0,0000,05). 4) Artinya terdapat pengaruh dukungan sosial dengan coping stress secara signifikan nilai p-value sebesar (0,0000,05). 5) Artinya terdapat pengaruh coping stress dengan psychological well-being secara signifikan dan nilai p-value sebesar 0,0000,05. 6) Artinya terdapat pengaruh religiusitas dengan coping stress melalui psychological well-being secara signifikan dan nilai p-value sebesar 0,0410,05. 7) Artinya terdapat pengaruh dukungan sosial dengan coping stress melalui psychological well-being secara signifikan dan nilai p-value sebesar 0,0030,05